Persepsi Siswa Terhadap Perpustakaan Sejarah di SMA Adabiah Padang - Silvia Oktaviana; Zafri Zafri (Jurusan Sejarah FIS UNP, 2020)
This study discusses students' perceptions of the history library at Adabiah Padang High School. The purpose of this study was conducted, namely to determine the percentage of students who have a positive impression of the function of library history and the intensity of student perceptions on each item of library function. This type of research is quantitative descriptive research. The subjects in this study were all students of class X, XI, and XII of Adabiah Padang high school in 2019/2020. The instrument used was a questionnaire distributed to 86 students. In this study, researchers focused more on how to utilize libraries based on library functions, namely the educational function, informative function, recreational function, and research function. From the results of research conducted using the TCR formula that each library function is classified as good, but there is one lowest percentage found in the informative function that is 66%. from the description of students' perceptions of the historical library as a whole is in the good category, where the TCR results are 71%. while the least percentage is in the sufficient category. In general, students' impressions of the history library are good, but there are some activities that have not been carried out because judging from the short break time, the lack of socialization of students in the modern era, and students are more passive than active.